Пылает город Кандагар...: Стихи и песни / В. Г. Верстаков - Верстаков Виктор Глебович (Мол. гвардия, 1990)
Экземпляры: ЧЗ (20160406) / Инвентарный номер: 26580 / Цена: 0.35 / Сис.шифр: Р2 / Авт.знак: В35 / ГРНТИ: 17 / ББК: Р2